A case of adult‐onset periodic fever, aphthous stomatitis, pharyngitis, and adenitis syndrome in Japan. (2nd May 2017) - Yasuura, Shusuke; Harada, Yukinori
Abstract: Adult‐onset periodic fever, aphthous stomatitis, pharyngitis, and adenitis (PFAPA) syndrome is rare. We report the case of a 23‐year‐old woman with PFAPA syndrome in Japan. Her symptoms lasted for approximately 5 days in each period regardless of nonsteroidal anti‐inflammatory drug or antibiotic treatment. She was diagnosed with PFAPA syndrome based on her periodic self‐limiting symptoms and no evidence of other febrile diseases. Following cimetidine therapy, her periodic symptoms diminished. PFAPA syndrome should be considered in patients presenting with periodic fever and upper respiratory symptoms regardless of their age or ethnicity.